1994
DOI: 10.1111/j.1748-1716.1994.tb09728.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged bleeding time during nitric oxide inhalation in the rabbit

Abstract: During a study on the modulatory effect of inhaled nitric oxide (NO) on the airway, we observed an increased bleeding tendency. Therefore, we studied bleeding time and blood rheology in rabbits during inhalation of 3, 30 and 300 parts per million (ppm) NO. The rabbits were intubated during neurolept anaesthesia and were ventilated mechanically. The bleeding time was significantly increased after 15 min of inhalation of 30 ppm NO, from 51 +/- 5 to 72 +/- 7 s (mean +/- SEM, P < 0.001, n = 7). However, there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(41 citation statements)
references
References 21 publications
1
39
1
Order By: Relevance
“…One hypothesis is that the hyperosmolarity per se may inactivate the NO molecule. Further support for this comes from previous rabbit studies, where inhalation of NO at a concentration of 300 ppm decreased the MAP and the lung compliance [6,18]. In this study, after hypertonic saline nebulization, these effects were abolished.…”
Section: Discussionsupporting
confidence: 69%
“…One hypothesis is that the hyperosmolarity per se may inactivate the NO molecule. Further support for this comes from previous rabbit studies, where inhalation of NO at a concentration of 300 ppm decreased the MAP and the lung compliance [6,18]. In this study, after hypertonic saline nebulization, these effects were abolished.…”
Section: Discussionsupporting
confidence: 69%
“…19,25,26 In this study, iNO therapy had a significant effect on BBB dysfunction as measured by EB extravasation, so the shown reduction of brain water content is most probably because of a combination of reduction of vasogenic and cytotoxic edema formation. Furthermore, NO inhalation has been shown to exert anti-platelet activity [38][39][40] and to act anti-inflammatorily. 29,41 We previously showed that microthrombus formation occurs in our model of murine CCI and further deteriorates CBF; 42 in the same study leukocyte-platelet aggregates were detected in cerebral venules.…”
Section: Discussionmentioning
confidence: 99%
“…inhaled NO [45,46]. The clinical significance of this remains unclear but inhaled NO should probably be used with caution in patients with bleeding diathesis and intracranial haemorrhage [47].…”
Section: Background and Controversiesmentioning
confidence: 99%